ISAACUS ZABANIUS' EXISTENTIA ATOMORUM: Searching for a New Historical-Philosophical Context. - GUBA, ÁGOSTON (Filozofia, 2020)
In this paper I deal with the Existentia atomorum (Wittenberg 1667) written by Isaacus Zabanius (1632 - 1707) when he was professor of the College of Eperjes / Prešov in Upper Hungary. After giving a short biography of Zabanius, I critically examine the results of the earlier Hungarian scholarship on the Existentia atomorum presented by János Erdélyi, Jolán Zemplén and András Mészáros. I point out that their interpretations were seriously affected by a given narrative, moreover in certain cases it has even led to factual mistakes. Finally, I try to place the work into a different historical and philosophical context rooted in the Wittenbergian background. The fact that the Existentia atomorum, unlike his other writings in the same period, was published in Wittenberg may explain its apologetic character. I argue that in this Wittenbergian context the main feature of the work can be found in a kind of minimalism concerning atomic theory.